2013
DOI: 10.1371/journal.pone.0056097
|View full text |Cite
|
Sign up to set email alerts
|

MtrR Control of a Transcriptional Regulatory Pathway in Neisseria meningitidis That Influences Expression of a Gene (nadA) Encoding a Vaccine Candidate

Abstract: The surface-exposed NadA adhesin produced by a subset of capsular serogroup B strains of Neisseria meningitidis is currently being considered as a vaccine candidate to prevent invasive disease caused by a hypervirulent lineage of meningococci. Levels of NadA are known to be controlled by both transcriptional regulatory factors and a component of human saliva, 4-hydroxyphenylacetic acid. Herein, we confirmed the capacity of a DNA-binding protein termed FarR to negatively control nadA expression. We also found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…It is also an active component of some Chinese herb such as Aster tataricus and Rhodiola rosea , as well as an intermediate product of chemical synthesis of atenolol (β-receptor blocking agent) and puerarin (active component of Lobed Kudzuvine Root ). Some previous studies reported that 4-HPA controlled the NadA gene expression and could become a potential hypopigmenting agent [23,24,25]. Our results suggested that 4-HPA was a good inhibitor of hypertonicity, hypoxia, or both of the two-induced HIF-1α expression.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It is also an active component of some Chinese herb such as Aster tataricus and Rhodiola rosea , as well as an intermediate product of chemical synthesis of atenolol (β-receptor blocking agent) and puerarin (active component of Lobed Kudzuvine Root ). Some previous studies reported that 4-HPA controlled the NadA gene expression and could become a potential hypopigmenting agent [23,24,25]. Our results suggested that 4-HPA was a good inhibitor of hypertonicity, hypoxia, or both of the two-induced HIF-1α expression.…”
Section: Discussionsupporting
confidence: 62%
“…Some previous studies reported that 4-HPA, a metabolite of aromatic amino acid catabolism that is secreted in saliva, controlled the NadA gene expression and could become a potential hypopigmenting agent [23,24,25]. We also found that Aster tataricus extract and 4-HPA could inhibit HIF-1α expression in our preliminary experiments.…”
Section: Introductionsupporting
confidence: 73%
“…MtrR has also recently been implicated in the regulation of nadA expression in the meningococcus. NadA is a major surface antigen and a virulence factor involved in adherence and invasion [26,27]. It is also a component of the multicomponent vaccine developed to target serogroup B meningococci (Bexsero) and the likely target of corresponding protection that has been demonstrated against isolates of the original UK W:cc11 strain [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that nadA expression levels are mainly regulated by the Neisseria adhesin A Regulator (NadR) [ 7 ]. Although additional factors influence nadA expression, we focused on its regulation by NadR, the major mediator of NadA phase variable expression [ 8 , 9 ]. Studies of NadR also have broader implications, since a genome-wide analysis of MenB wild-type and nadR knock-out strains revealed that NadR influences the regulation of > 30 genes, including maf genes, from the m ultiple a dhesin f amily [ 10 ].…”
Section: Introductionmentioning
confidence: 99%